Celastraceae endémicas del Perú - León, Blanca (2006)
The Celastraceae are represented in Peru by eight genera and 29 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly lianas. Here we recognize four endemic taxa in two genera. Endemic Celastraceae grow in Desert Shrubland and Mesoandean regions, between 600 and 3300 m elevation. We applied IUCN categories and criteria to two species. One endemic Celastraceae is represented within Peru’s protected areas system.